Identification of bioactive constituents in indigenously grown Calotropis gigantea and Moringa oleifera fractions by HPLC (Acta Scientiarum. Biological Sciences, 2024)
Plants are the most ubiquitous sources of bioactive organic compounds on earth. Active metabolites such as phytochemicals from medicinal plants have been investigated for the development of cutting-edge and biodegradable potent drugs as an alternative to ineffective modern treatment. The medicinal plants Calotropis gigantea and Moringa oleifera contain biochemical constituents that may have therapeutic qualities. The bioactive components in C. gigantea and M. oleifera leaves were analyzed using HPLC. HPLC analysis of several leaf fractions unveils the presence of quercetin, gallic acid, coumaric acid, caffeic acid, chlorogenic acid, ferulic acid, cinnamic acid, sinapinic acid, and vanillic acid in both plants. Furthermore, phytochemical study of these plants revealed the presence of alkaloids, flavonoids, saponins, tannins, terpenoids, and glycosides in different solvents. The identified chemicals have reported antioxidant and antitumor properties. The current study's findings suggest that C. gigantea and M. oleifera could be used as a source for a credible antioxidant agent that might later be isolated and used as lead candidates for the fabrication of antioxidant drugs that help stop or limit free radical damage and counteract oxidative stress, thereby preventing a variety of chronic and degenerative diseases.